Spatial Supporting Capacity In Sustainable Development: Daya Dukung Ruang Dalam Pembangunan Berkelanjutan - Kunarto Kunarto; Budi Prasetyo (IHSA Institute, 2022)
Development is a process of processing natural resources and utilizing human resources by utilizing technology. It needs very mature and integrated planning by taking into account all points of view and perceptions that influence each other in carrying out the development. Sustainable development which is the goal of Law Number 32 of 2009 concerning Environmental Protection and Management should be a guideline for increasing the carrying capacity and capacity of the environment. Nature's ability to support life and tolerance for the substances that are put into it must have limitations, so humans as living beings who are part of the environment must protect the environment in which they live. The implementation of sustainable development pays attention to the availability of natural resources for future generations.